Collapse of Dollar Value-Its Impact in India - Ramachandran, A.; Maran, Maria Nayagam; Kavitha, N. (Indian Journal of Finance, 2008)
The study on "Collapse of Dollar Value - Its impact in India" will help us to learn the fluctuation of national economy and its related impact to the country and also for its industries. Now, what does a collapse in the value of the dollar mean for finances Many things, mostly bad but some potentially very good. The recent depreciation of US dollar has created quite a stir in the countries throughout the world. It is hard for most Americans to get a grasp on what has been happening with the dollar. It's not like the stock market where its price is quoted on the nightly news. The main reason for the rupee's appreciation since late 2006 has been a flood of foreign-exchange inflows, especially US dollars. However, the rupee's appreciation is alarming exporters, as it makes their products more expensive in overseas markets and erodes their international competitiveness. Although the FDI and NRI investment became high in its volume so that dollar demand has been gone down against Dollar where it has its heavy impact on the both import and exports. All these trends and impact may cause to heavy inflation in the economy in India. How this impact has been drive its impact positively or negatively in Indian economy is really good case to study and analyze.